The mediating role of willingness to seek help on the relationship between peer victimization and mental health outcomes. (September 2021) - Williford, Anne; Sharp, Julia L.; Fout, Alex; Schafer, Casey; Shi, Xiaosong; Isen, Debbie
Highlights: Peer victimization is common in childhood with adverse mental health impacts. Help-seeking from adults in response to peer victimization is highly encouraged. Help-seeking may help to explain the impact of peer victimization on mental health. Mediational models show effects for self-esteem but not depressive or anxiety symptoms. Willingness to seek help may impact self-esteem after peer victimization. Abstract: Peer victimization is a common negative experience in childhood that can result in a number of harmful consequences, including a range of mental health challenges. Consequently, adult intervention, especially for elementary school-aged children, has been identified as a key ingredient in the prevention of and intervention with acts of aggression and peer victimization. However, children are not always willing to seek help from adults at school in response to peer victimization exposure, suggesting variability in children's responses to being targeted by peers. A potential mediating pathway may exist where victimization exposure impacts children's willingness to seek help from adults at school, which in turn may have an impact on their adjustment, including mental health outcomes. However, little is known about the role of children's willingness to seek help in the link between exposure and negative mental health outcomes. In the present study, we examine 1) if willingness to seek help from teachers mediates the relationship between peer victimization exposure and mental health outcomes (depressive symptoms, anxiety symptoms, and self-esteem); and 2) the mediation effects for boys and girls. Based on a sample of 960 3rd-5th grade students from seven elementary schools, results suggest that, while increased peer victimization was associated with lower willingness to seek help and worse mental health outcomes, meditational effects were only found for self-esteem for both boys and girls. Implications for practice in schools are discussed in terms of potential prevention and intervention practices in schools.